Diversity of ESBL-producing E. coli in various water and sediment types - Leon Maric; Maja Rupnik; Sandra Janezic (PLoS ONE, 2025)
Antimicrobial resistance is a major global health threat, and aquatic ecosystems serve as critical interfaces between human activity and the environment, providing reservoirs and pathways for the spread of resistant bacteria. In this study, we investigated the prevalence and diversity of ESBL-producing Escherichia coli across multiple aquatic environments in Slovenia by analysing water, sediment, and wastewater treatment plant (WWTP) influent samples collected between June 2023 and April 2024. ESBL-producing E. coli was detected in 93% of WWTP influents, 61% of water, and 35% of sediment samples. From 315 positive samples, 564 isolates were subjected to whole genome sequencing. In total, 134 MLST-sequence types (STs) were identified, with globally prevalent lineages (ST131, ST38, ST10, ST69, ST1193) occurring across regions and sample types. Clonally related isolates occurred in geographically distant sites, and persistent strains were observed over time, suggesting both local persistence and broader dissemination. Fourteen distinct ESBL genes were detected, predominantly plasmid-encoded bla CTX-M-15 . Water samples captured the greatest ST diversity, whereas sediment and WWTP influents provided complementary insights. Combining sample types improved detection of overall diversity, with water and sediment or WWTP samples providing the most comprehensive overview. Our findings demonstrate widespread and dynamic dissemination of ESBL-producing E. coli in Slovenian aquatic environments and emphasize the value of integrated sampling strategies for effective surveillance.